Relationship between individual alpha peak frequency and attentional performance in a multiple object tracking task among ice-hockey players. - Yanhui Zhang; Yingzhi Lu; Dandan Wang; Chenglin Zhou; Chang Xu (PLoS ONE)
Individual alpha peak frequency (IAPF), the discrete frequency with the highest power value in the alpha oscillation range of the electroencephalogram, is a stable neurophysiological marker and is closely associated with various cognitive functions, including aspects of attention and working memory. However, the relationship between IAPF and attentional performance as well as the effects of engaging attention on IAPF are unknow. Here, we examined whether IAPF values were associated with attentional performance by evaluating accuracy during the performance of a multiple object tracking (MOT) task, a well-established paradigm for investigating goal-driven attention in dynamic environments, and whether engagement in the task affected IAPF values. In total, 18 elite players and 20 intermediate players completed the study. Resting electroencephalogram recordings were obtained for 120 s while players kept their eyes open and an additional 120 s while players' eyes were closed, before and again after performing the MOT task. Tracking accuracy in the MOT task and IAPF values before and after the MOT task were analyzed. As expected, tracking accuracies were higher in elite players than in intermediate-level players. Baseline IAPF values were significantly and positively correlated with the accuracy of target tracking in the MOT task. IAPF values were higher in elite than intermediate players in both the eyes open and closed conditions and both before and after MOT task performance. Interindividual IAPF values did not differ before and after the MOT task. These findings indicate that IAPF is a stable marker, without intraindividual changes associated with engagement in the MOT task. Elite players had higher IAPF values and exhibited more accurate MOT performance than intermediate-level players; thus, baseline IAPF values may be useful to predict attentional performance in the MOT task among athletes.